Micro-RNA-21 (biomarker) and global longitudinal strain (functional marker) in detection of myocardial fibrotic burden in severe aortic valve stenosis: a pilot study. Issue 1 (December 2016) - Fabiani, Iacopo; Scatena, Cristian; Mazzanti, Chiara; Conte, Lorenzo; Pugliese, Nicola; Franceschi, Sara; Lessi, Francesca; Menicagli, Michele; De Martino, Andrea; Pratali, Stefano; Bortolotti, Uberto; Naccarato, Antonio; et al.
Abstract Aims Myocardial fibrosis (MF) is a deleterious consequence of aortic valve stenosis (AVS). Global longitudinal strain (GLS) is a novel left ventricular (LV) functional parameter potentially useful to non-invasively estimate MF. MicroRNAs (miRNAs) are non-coding small ribonucleic acids (RNA) modulating genes function, mainly through RNA degradation. miRNA-21 is a biomarker associated with MF in pressure overload. The aim of the present study was to find an integrated algorithm for detection of MF using a combined approach with both bio- and functional markers. Methods Thirty-six patients (75.2 ± 8 y.o.; 63 % Female) with severe AVS and preserved LV ejection fraction (EF), candidate to surgical aortic valve replacement (sAVR) were enrolled. Clinical, bio-humoral evaluation (including plasmatic miRNA-21 collected using specific tubes, PAXgene, for stabilization of peripheral RNA) and a complete echocardiographic study, including GLS and septal strain, were performed before sAVR. Twenty-eight of those patients underwent sAVR and, in 23 of them, an inter-ventricular septum biopsy was performed. Tissues were fixed in formalin and embedded in paraffin. Sections were stained with Hematoxylin and Eosin for histological evaluation and with histochemical Masson trichrome for collagen fibers. The different components were calculated and expressed as micrometers2 . To evaluate tissue miRNA components, sections 2-μm thick were cut using a microtome blade for each slide. Regression analysis was performed to test association between dependent variable and various predictors included in the model. Results Despite a preserved EF (66 ± 11 %), patients presented altered myocardial deformation parameters (GLS −14, 02 ± 3.8 %; septal longitudinal strain, SSL −9.63 ± 2.9 %; septal longitudinal strain rate, SL-Sr −0.58 ± 0.17 1/s; Septal Longitudinal early-diastolic strain rate, SL-SrE 0.62 ± 0.32 1/s). The extent of MF showed an inverse association with both GLS and septal longitudinal deformation indices (GLS: R2  = 0.30; p = 0.02; SSL: R2  = 0.36; p = 0.01; SL-Sr: R2  = 0.39; p < 0.001; SL-SrE: R2  = 0.35; p = 0.001). miRNA-21 was mainly expressed in fibrous tissue (p < 0.0001). A significant association between MF and plasmatic miRNA-21, alone and weighted for measures of structural (LVMi R2  = 0.50; p = 0.0005) and functional (SSL R2  = 0.35; p = 0.006) remodeling, was found. Conclusions In AVS, MF is associated with alterations of regional and global strain. Plasmatic miRNA-21 is directly related to MF and associated with LV structural and functional impairment.